School Organizational Climate and Leadership Styles among School Admin-istrators: Effect on the Teacher’s Level of Performance - Pulumbarit, Jaime (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study's main goal was to determine the effect of the school's organizational climate and administrator's leadership styles on the teacher's level of performance in the selected Apostolic Vicariate of Bulacan (AVB) Parochial Schools. The teachers at six chosen AVB parochial schools served as the study's primary respondents. The tool utilized was a four-part questionnaire about the culture of the organization, the leadership style, and the effectiveness of the teachers. Frequency distribution, standard deviation, descriptive measures, and standard linear regression analysis were the statistical techniques utilized to quantify and infer the relationship between the relevant variables. The findings showed that gender and the highest educational degree are important predictors of instructors' performance levels at the 0.05 significance level. It was also determined that leadership style and organizational climate had no significant impacts on the teachers' performance. Suggestions on a collaborative effort by the administration, teachers, and students should be looked into and evaluated for the further enhancement of this study.